Historical Field Lecture As a Strengthening Of Character Education In Stkip Pgri Lubuklinggau Students - Agus Susilo; Ratna Wulansari (Criksetra: Jurnal Pendidikan Sejarah, 2019)
Historical Education is a part of learning that examines the past that is examined based on the present. Universities have programs in the development of Historical Education for their students. Historical Field Lecture Program for students of Historical Education Study Program STKIP Lubrilinggau PGRI is a program that synergizes with compulsory courses for students. The program has the purpose of increasing the insight and knowledge of prospective history teachers on the studies taken by these students. But it cannot be abandoned that History Field Lecture is part of strengthening character education. Character education is a study in the 2013 curriculum that emphasizes attitudes in carrying out the teaching and learning process. Students who visit historical sites are expected to gain direct knowledge and insights from the objects they visit, and be able to absorb the knowledge gained from the field studies. The values of local wisdom contained in historical heritage are a reflection and action material to continue to develop and maintain high-value historical heritage. although the era of globalization will not eliminate the noble identity of the nation and who have good personality values for the progress of the nation. The results of the Historical Field Lecture visits by students of the STKIP History Education Study Program PGRI Lubuklinggau are expected that historical learning in the field can inspire students to learn more about the wider history. Apart from that, being able to absorb knowledge of historical heritage forms the character of good students, who are innovative, hard-working, and have global insight.